2008
DOI: 10.20506/rst.27.3.1838
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of peste des petits ruminants in sheep and goats of southern peninsular India

Abstract: This paper presents the results of a seroepidemiological study carried out between July 2006 and March 2007 to detect the presence of antibodies to peste des petits ruminants (PPR) virus in randomly collected serum samples from sheep and goats in southern peninsular India. The authors used a competitive enzyme-linked immunosorbent assay with a monoclonal antibody developed against a neutralising epitope of the haemagglutinin (HA) protein of the virus. A total of 1,492 sheep sera and 2,068 goat sera collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 10 publications
1
25
2
Order By: Relevance
“…The reported prevalence of PPR in goats at present study was 1.37% and was in opposite with the results higher prevalence reported by Al-Dubaib (26) (13,(19)(20)(21)(22). Aunque puede no haber una variación significativa en las tasas de incidencia de la enfermedad, se ha establecido una mayor mortalidad en los caprinos infectados con PPRV que en ovinos (23).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of PPR in goats at present study was 1.37% and was in opposite with the results higher prevalence reported by Al-Dubaib (26) (13,(19)(20)(21)(22). Aunque puede no haber una variación significativa en las tasas de incidencia de la enfermedad, se ha establecido una mayor mortalidad en los caprinos infectados con PPRV que en ovinos (23).…”
Section: Discussioncontrasting
confidence: 99%
“…Soundararajan et al (18) also showed a higher mortality rate among infected goats than sheep in a large organized farm. However, higher seroprevalence in sheep as compared to goats has been observed in some other studies (13,(19)(20)(21)(22) Although sheep and goats may not vary significantly in qualifications of disease incidence but a higher mortality rate in PPRV infected goats than in sheep has been established (23).…”
Section: Discussionmentioning
confidence: 90%
“…Outbreaks are more common in sheep in South India and in goats in North India [4,19,20,29,36]. To control the disease, two vaccine strains, Arasur and Sungri, were initially characterized, and the latter has been commercialized.…”
Section: Discussionmentioning
confidence: 99%
“…Although, presence of PPR-like disease has been suspected earlier in retrospective study (Taylor et al, 2002), its presence was confirmed in India in1987 from Arasur village of Villupuram district of Tamil Nadu (Shaila et al, 1989). Currently, PPR outbreaks are being reported regularly from different parts of the country (Chauhan et al, 2011;Kerur et al, 2008;Muthuchelvan et al, 2014;Nanda et al, 1996;Raghavendra et al, 2008;Singh et al, 2004a). The disease outbreak status for the period between 2009 and 2014 is depicted in Figure 1.…”
Section: The Diseasementioning
confidence: 99%